The age of synthesis : 1800-1895 - Spangenburg, Ray, 1939-; Moser, Diane, 1944-; Spangenburg, Ray, 1939- (New York : Facts on File, 2004)
Examines the role of science in the Industrial Revolution, its establishment as a popular discipline, and discoveries in the areas of atoms and the elements, chemistry, evolution, and energy
Rev. ed. of: The history of science in the nineteenth century. 1994
Keywords: Science -- History -- 19th century -- Juvenile literature; Science -- History